Bureaucratic Barrier Mitigation Strategy in Smart City Implementation in Cimahi City - Genis Arivanny Putri Sekarsari (Dalihan Na Tolu: Jurnal Hukum, Politik dan Komunikasi Indonesia, 2026)
The implementation of Smart City policies often faces non-technical obstacles in the form of structural rigidity and resistance from the government bureaucratic work culture. This study aims to identify clusters of bureaucratic obstacles in Smart City implementation in Cimahi City and formulate comprehensive mitigation strategies. Using qualitative research methods with a descriptive approach, data were collected through in-depth interviews with key informants from the Cimahi City Communication and Information Technology Office (Diskominfo) and the Regional Development Planning Agency (Bappeda), system observations, and documentation studies of supporting regulations. The results indicate that smart city implementation is hampered by six main factors: sectoral egos that trigger data silos, the clash between rigid structures and digital dynamics, apparatus resistance to change, limited human resource ICT competencies, a reductive mindset toward "ICT projects," and weak leadership commitment and budget sustainability. To address these issues, this study formulates four comprehensive mitigation strategies: (1) digital transformation through a Single Sign-On (SSO) system and SPBE-based data interconnection; (2) technical guidance on digital literacy and a shift in the mindset of civil servants (ASN) to a service-oriented one; (3) strengthening macro regulations in the RPJMD/RPJPD and developing digital standard operating procedures (SOPs) to reduce bureaucracy (debureaucratization); and (4) institutionalizing public participation spaces and the Pentahelix Collaboration involving local academics such as Jenderal Achmad Yani University. In conclusion, the success of Smart City in Cimahi City requires holistic bureaucratic reform to transform technology from a mere administrative formality into a fast, agile, and accountable public service engine.